(untitled) (Revista História & Perspectivas, 2011)
Este texto discute a posição política privatista assumida pelo empresariado da indústria pesada brasileira, especialmente aqueles representados pela ABDIB e pelo IBS, no final de 1980. Procuramos demonstrar que essa não foi uma posição natural do grande empresariado; ao contrário, historicamente esse dois setores apoiaram os investimentos do Estado, inclusive, a criação de empresas estatais, como fica claro quando verificamos a posição do empresariado frente ao II PND. Foi a crise fiscal do Estado brasileiro, manifesta na sua dificuldade em continuar financiando seus projetos industriais ao mesmo tempo em que financiava a expansão das indústrias privadas que acabou determinando a mudança de posição do grande empresariado industrial brasileiro. PALAVRAS-CHAVE: Indústria pesada brasileira. Privatizações. Crise fiscal. ABSTRACT: This paper discusses the pro-privatization position taken by Brazil’s heavy industry business community, in particular those represented by ABDIB and IBS, in the late ’80s. We argue that the defense of privatization was not a natural position of big business; on the contrary, the heavy industry sector, as for instance the steel industry, had historically supported state investments including the creation of state companies, as evidenced by its favorable position regarding the II PND. It was the fiscal crisis of the Brazilian state, which found itself unable to keep financing its own industrial projects at the same time it funded the expansion of the private sector, which eventually determined the political shift of the Brazilian’s industrial business in favor of a smaller role of the state in the economy. KEYWORDS: Brazilian heavy industry. Privatization. Fiscal crisis.